Morphological and Functional Changes of Corneal Nerves and Their Contribution to Peripheral and Central Sensory Abnormalities - Guerrero-Moreno, Adrian; Baudouin, Christophe; Melik Parsadaniantz, Stéphane; Réaux-Le Goazigo, Annabelle (Frontiers in Cellular Neuroscience, 2020)
The cornea is the most densely innervated and sensitive tissue in the body. The cornea is exclusively innervated by C- and A-delta fibers, including mechano-nociceptors that are triggered by noxious mechanical stimulation, polymodal nociceptors that are excited by mechanical, chemical and thermal stimuli, and cold thermoreceptors that are activated by cooling. Noxious stimulations activate corneal nociceptors whose cell bodies are located in the trigeminal ganglion (TG) and project central axons to the trigeminal brainstem sensory complex. Ocular pain, in particular, that driven by corneal nerves, is considered to be a core symptom of inflammatory and traumatic disorders of the ocular surface. Ocular surface injury affecting corneal nerves and leading to inflammatory responses can occur under multiple pathological conditions, such as chemical burn, persistent dry eye, and corneal neuropathic pain as well as after some ophthalmological surgical interventions such as photorefractive surgery. This review depicts the morphological and functional changes of corneal nerve terminals following corneal damage and dry eye disease (DED), both ocular surface conditions leading to sensory abnormalities. In addition, the recent fundamental and clinical findings of the importance of peripheral and central neuroimmune interactions in the development of corneal hypersensitivity are discussed. Next, the cellular and molecular changes of corneal neurons in the TG and central structures that are driven by corneal nerve abnormalities are presented. A better understanding of the corneal nerve abnormalities as well as neuroimmune interactions may contribute to the identification of a novel therapeutic targets for alleviating corneal pain.